EFL Pre-Service Teachers’ Perception Toward Process Approach in Teaching Writing At SMP Negeri 2 Banjar - Pradnyana, I Ketut Putra; Dewi, Ni Luh Putu Eka Sulistia; Agustini, Dewa Ayu Eka (The Art of Teaching English as a Foreign Language (TATEFL), 2020)
The current study was intended to identify the English Foreign Language (EFL) pre-service teachers’ perception toward process approach in teaching writing at SMP Negeri 2 Banjar. This study was a basic interpretative study. In collecting the data, this study used questionnaire and interview. The study was followed by 5 preservice teachers at SMP Negeri 2 Banjar. The data from the questionnaire were analyzed descriptively and the data from the interview were analyzed using O’Connor and Gibson’s guidance. The study found that the teachers have positive and very positive perception towards process approach in teaching writing. It was also found that during the implementation of process approach, the teachers were aware of several challenges encountered, namely the limitations of students in developing ideas, weaknesses of students in aspects of language and students requires times to finish writing. This study concludes that the pre-service English teachers had a positive perception towards using process approach in teaching writing.